Cryogenically structured gelatin-based hydrogel as a resorbable macroporous matrix for biomedical technologies - A. M. Grigoriev; Yu. B. Basok; A. D. Kirillova; V. A. Surguchenko; N. P. Shmerko; V. K. Kulakova; R. V. Ivanov; V. I. Lozinsky; A. M. Subbot; V. I. Sevastianov (Вестник трансплантологии и искусственных органов)
Objective: to investigate the biological properties of a matrix made of cryogenically structured hydrogel in the form of a macroporous gelatin sponge, as well as the possibility of creating cell-engineered constructs (CECs) on its basis. Materials and methods. The main components of the cryogenically structured hydrogel were gelatin (type A) obtained from porcine skin collagen, N-(3-dimethylaminopropyl)-N’-ethylcarbodiimide, (EDC) and urea (all from Sigma-Aldrich, USA). Surface morphology was examined using scanning electron microscopy (SEM). The degree of swelling in water of the samples was determined by gravimetric method. Cytotoxicity was studied on NIH3T3, a fibroblast cell line isolated from a mouse, and on human adipose-derived mesenchymal stem/stromal cells (hAMSCs) using IncuCyte ZOOM (EssenBioscience, USA). The metabolic activity of hAMSCs was assessed using PrestoBlue™ reagents (Invitrogen™, USA). To create CECs, we used hAMSCs, human hepatocellular carcinoma cell line HepG2 or human umbilical vein endothelial cell lines EA.hy926. Albumin content in the culture medium was determined by enzyme immunoassay. Ammonia metabolism rate was assessed after 90 minutes of incubation with 1 mM ammonium chloride (Sigma-Aldrich, USA) diluted in a culture medium on day 15 of the experiment. Results. Obtaining a cryogenically structured hydrogel scaffold in the form of macroporous gelatin sponge included freezing an aqueous solution of a gelatin+urea mixture, removal of polycrystals of frozen solvent by lyophilization, extraction of urea with ethanol and treatment of the cryostructurate with an ethanol solution of EDC. Scanning electron microscopy identified three types of pores on the carrier surface: large (109 ± 17 μm), medium (39 ± 10 μm), and small (16 ± 6 μm). The degree of swelling in water of the matrix samples was 3.8 ± 0.2 g H2O per 1 g of dry polymer. The macroporous gelatin sponge as a part of CEC was found to have the ability to support adhesion and proliferation of hAMSCs, EA.hy926 and HepG2 for 28, 15 and 9 days, respectively. Albumin secretion and ammonia metabolism when HepG2 cells were cultured on the gelatin sponge were detected. Conclusion. The use of a matrix made from macroporous cryogenically structured gelatin-based hydrogel for tissue engineering products is shown to be promising using a cell-engineered liver construct as a case.